Media Representations of Water Issues as Health Risks. Issue 7 (3rd October 2019) - Mayeda, Alyssa M.; Boyd, Amanda D.; Paveglio, Travis B.; Flint, Courtney G.
ABSTRACT: Water is a critical natural resource for sustaining human life. Media representations are a factor in the formation of public risk perceptions and could influence water conservation and health promotion behaviors. The objective of this research is to identify how newspaper media in four Western U.S. states frame the public health risks associated with water resources. Researchers conducted a content analysis of 326 newspaper articles from eight major newspapers focusing on water resource issues published during a three-year period between January 2012 and December 2014. Results indicate that health risks associated with water are seldom mentioned, and that the risks most frequently covered with regard to water resources are those with direct and immediate impacts to area residents. Findings suggest that media coverage may not be consistent with the nature of health impacts associated with water, which often are long-term.